Evaluation Of The E-Peken Program In Supporting The Sustainability Of UMKM In Surabaya - Annisa Mifthalia As-Zahra; Rizky Septian Agusti; Rangga Wahyu Anugrah (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This study aims to evaluate the Economic Empowerment and Economic Resilience Program of Surabaya (E-Peken) in supporting the sustainability of Micro, Small, and Medium Enterprises (MSMEs) in the city of Surabaya. Although MSMEs contribute significantly to the national Gross Domestic Product (GDP), the E-Peken program experienced a significant decline in turnover for three consecutive months in 2023. This study uses the CIPP (Context, Input, Process, Product) evaluation model to analyze the effectiveness of the program. The results show that this program still faces various obstacles, including low digital literacy, lack of infrastructure access, and inactivity of the State Civil Apparatus (ASN) in shopping through the platform. Therefore, a more adaptive and responsive strategy is needed to increase MSME participation and the effectiveness of the E-Peken program.